Valproic Acid Induces Endothelial-to-Mesenchymal Transition-Like Phenotypic Switching - Murugavel, Shamini; Bugyei-Twum, Antoinette; Matkar, Pratiek N.; Al-Mubarak, Husain; Chen, Hao H.; Adam, Mohamed; Jain, Shubha; Narang, Tanya; Abdin, Rawand M.; Qadura, Mohammad; Connelly, Kim A.; Leong-Poi, Howard; et al. (Frontiers in Pharmacology, 2018)
Valproic acid (VPA), a histone deacetylase (HDAC) inhibitor, is a widely used anticonvulsant drug that is currently undergoing clinical evaluation for anticancer therapy due to its anti-angiogenic potential. Endothelial cells (ECs) can transition into mesenchymal cells and this form of EC plasticity is called endothelial-to-mesenchymal transition (EndMT), which is widely implicated in several pathologies including cancer and organ fibrosis. However, the effect of VPA on EC plasticity and EndMT remains completely unknown. We report herein that VPA-treatment significantly inhibits tube formation, migration, nitric oxide production, proliferation and migration in ECs. A microscopic evaluation revealed, and qPCR, immunofluorescence and immunoblotting data confirmed EndMT-like phenotypic switching as well as an increased expression of pro-fibrotic genes in VPA-treated ECs. Furthermore, our data confirmed important and regulatory role played by TGF-signaling in VPA-induced EndMT. Our qPCR array data performed for 84 endothelial genes further supported our findings and demonstrated 28 significantly and differentially regulated genes mainly implicated in angiogenesis, endothelial function, EndMT and fibrosis. We, for the first time report that VPA-treatment associated EndMT contributes to the VPA-associated loss of endothelial function. Our data also suggest that VPA based therapeutics may exacerbate endothelial dysfunction and EndMT-related phenotype in patients undergoing anticonvulsant or anticancer therapy, warranting further investigation.